Research on Optical/Electric Hybrid Switching Technique for Space-Integrated-Ground Information Network - Shanghong ZHAO; Cong PENG; Yongjun LI; Hai LI (天地一体化信息网络)
Space-integrated-ground information network will face the challenges of heterogeneous links, multi-granularity of information and limited resources in the process of networking.The problems can be solved by data switching design.The architecture of space-integrated-ground information network was described, and the present situation of multi-granularity service hybrid switching was analyzed.Based on this, the idea of hybrid optical/RF/packet switching was proposed, i.e., hybrid switching structure design, optical switching based on four-wave mixing eff ect, broadband confi gurable RF channelized switching, packet high-speed switching based on software radio idea, laser/RF heterogeneous link optical domain aggregation and grooming and enhanced general multi-protocol label switching design.